The Choice of Currency in the Foreign Trade of Italy - Giorgio Basevi; Daniela Cocchi; P. L. Lischi (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1985)
The main object of this study is an empirical analysis of the determinants of the choice of currency in setting payments and recepts for Italian foreign trade.
Keywords: 330